Students’ Perceptions of University Corruption in a Spanish Public University: A Path Analysis - Julián, Martín; Bonavia, Tomas (Frontiers in Psychology, 2022)
Most research on corruption in educational settings has focused on a cross-national and macro-level analysis; however, few papers have sought to explore individual perceptions that explain corruption in higher education. The present research aimed to disentangle students’ predictors of corrupt intention in a Spanish public university. A total of 933 undergraduate, postgraduate, and PhD students filled out an online survey measuring four corruption scenarios: favoritism, bribery, fraud, and embezzlement. Path analysis (PA) revealed that justifiability, risk perception, and perceived prevalence of corruption were significant factors in predicting corrupt intention. Moreover, willingness to report a corrupt act was predicted by corrupt intention, justifiability, and risk perception. Corrupt behavior is a complex phenomenon explained not only by peers’ behavior, but also by their individual justifications and perception of risk. Education is not free of corruption, and universities must address this urgent problem in order to avoid future economic, societal, and ethical problems.